Enhancing emotional experiences to dance through music: the role of valence and arousal in the cross-modal bias - Christensen, Julia F.; Gaigg, Sebastian B.; Gomila, Antoni; Oke, Peter; Calvo-Merino, Beatriz (Frontiers in Human Neuroscience, 2014)
It is well established that emotional responses to stimuli presented to one perceptive modality (e.g. visual) are modulated by the concurrent presentation of affective information to another modality (e.g. auditory) – an effect known as the cross-modal bias. However, the affective mechanisms mediating this effect are still not fully understood. It remains unclear what role different dimensions of stimulus valence and arousal play in mediating the effect, and to what extent cross-modal influences impact not only our perception and conscious affective experiences, but also our psychophysiological emotional response. We addressed these issues by measuring participants’ subjective emotion ratings and their Galvanic Skin Responses in a cross-modal affect perception paradigm employing videos of ballet dance movements and instrumental classical music as the stimuli. We chose these stimuli to explore the cross-modal bias in a context of stimuli (ballet dance movements) that most participants would have relatively little prior experience with. Results showed (i) that the cross-modal bias was more pronounced for sad than for happy movements, whereas it was equivalent when contrasting high vs. low arousal movements, and (ii) that movement valence did not modulate participants’ GSR, while movement arousal did such that GSR was potentiated in the case of low arousal movements with sad music and when high arousal movements were paired with happy music. Results are discussed in the context of the cross-modal affect perception literature and with regards to implications for the art community.